Programa de gestión integral del recurso hídrico en el Colegio del Bosque Bilingüe UAN-Bogotá, Colombia. (2022)
In search of reducing the water footprint in academic institutions, wastewater was characterized through different monitoring of the STAR at the school Colegio del Bosque Bilingüe-UAN, achieving the design of a monitoring and control program. The program was mainly influenced by the lack of personnel training, the absence of maintenance guides establishing routine work performed, analysis of parameters, frequency and period of analysis; this absence of information was reflected in the low removals of DBO5, conductivity, nitrites and nitrates. The hydrometeorological analysis identified that the area does not have rainfall greater than 5.56 mm, allowing for the design of a compact rainwater collector based on reused PET bottles and the use of a filter with an anthracite-based granular medium that removes organic matter and sedimentable solids for use in sinks, cisterns and common areas to reduce potable water consumption.